Let's evaluate each expression step by step.
Question 1: Evaluate the expression \(6a + 4b - 3c\) for \(a=3\), \(b=5\), and \(c=10\).
Substituting the values into the expression:
\[ 6(3) + 4(5) - 3(10) \]
Calculating each term:
\[ 6 \cdot 3 = 18 \] \[ 4 \cdot 5 = 20 \] \[ 3 \cdot 10 = 30 \]
Now combine the results:
\[ 18 + 20 - 30 = 38 - 30 = 8 \]
So, the answer for Question 1 is:
\[ \boxed{8} \]
Question 2: Evaluate the expression \(2.4x + 6.2y\) for \(x=3.5\) and \(y=1.8\).
Substituting the values into the expression:
\[ 2.4(3.5) + 6.2(1.8) \]
Calculating each term:
\[ 2.4 \cdot 3.5 = 8.4 \] \[ 6.2 \cdot 1.8 = 11.16 \]
Now combine the results:
\[ 8.4 + 11.16 = 19.56 \]
So, the answer for Question 2 is:
\[ \boxed{19.56} \]